Microscopic theory of current-induced skyrmion transport and its application in disordered spin textures - Östberg, Emil; Viñas Boström, Emil; Verdozzi, Claudio (Frontiers in Physics, 2024)
Magnetic skyrmions hold great promise for realizing compact and stable memory devices that can be manipulated at very low energy costs via electronic current densities. In this work, we extend a recently introduced method to describe classical skyrmion textures coupled to dynamical itinerant electrons. In this scheme, the electron dynamics is described via nonequilibrium Green's functions (NEGF) within the generalized Kadanoff-Baym ansatz, and the classical spins are treated via the Landau-Lifshitz-Gilbert equation. The framework is here extended to open systems, by the introduction of a non-interacting approximation to the collision integral of NEGF. This, in turn, allows us to perform computations of the real-time response of skyrmions to electronic currents in large quantum systems coupled to electronic reservoirs, which exhibit a linear scaling in the number of time steps. We use this approach to investigate how electronic spin currents and dilute spin disorder affects skyrmion transport and the skyrmion Hall drift. Our results show that the skyrmion dynamics is sensitive to the specific form of spin disorder, such that different disorder configurations leads to qualitatively different skyrmion trajectories for the same applied bias. This sensitivity arises from the local spin dynamics around the magnetic impurities, a feature that is expected not to be well captured by phenomenological or spin-only descriptions. At the same time, our findings illustrate the potential of engineering microscopic impurity patterns to steer skyrmion trajectories.